2011
DOI: 10.1902/jop.2010.100180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enamel Matrix Derivative on Vascular Endothelial Growth Factor Expression and Microvessel Density in Gingival Tissues of Periodontal Pocket: A Comparative Study

Abstract: EMD induces proliferation and viability and angiogenesis of human microvascular cells. Recent clinical and histologic studies found EMD to be useful as an adjunct to scaling and root planing in single-rooted teeth. Our findings may help to understand the mechanisms involved in soft tissue healing, through the ability of EMD to increase angiogenesis at periodontal pockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…Numerous investigations have elaborated on the potential for EMD to induce angiogenesis both in vitro and in animal models 32‐37 . Results from Sakoda et al demonstrated that EMD stimulates VEGF production partially via transforming growth factor‐β1 and fibroblast growth factor 2 in human gingival fibroblasts and that EMD‐induced VEGF production is regulated by extracellular regulated kinase, p38 mitogen‐activated protein kinase, and phosphatidylinositol 3 kinase/Akt pathways 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have elaborated on the potential for EMD to induce angiogenesis both in vitro and in animal models 32‐37 . Results from Sakoda et al demonstrated that EMD stimulates VEGF production partially via transforming growth factor‐β1 and fibroblast growth factor 2 in human gingival fibroblasts and that EMD‐induced VEGF production is regulated by extracellular regulated kinase, p38 mitogen‐activated protein kinase, and phosphatidylinositol 3 kinase/Akt pathways 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (13–16) have reported that the vascular endothelial growth factor (VEGF) plays an evident role in wound repair. In a study (13) on diabetic mice, impaired wound healing capacity was successfully corrected by administering the VEGF gene to the wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel matrix derivative (EMD) is a complex of low-molecular weight hydrophobic enamel proteins isolated from developing porcine tooth buds and consists by approximately 90% of amelogenin. An ability of EMD to stimulate angiogenesis in vivo was shown by both clinical and animal studies 11,12) . In vitro studies show that EMD possesses chemotactic ability, stimulates ECs migration, formation of vessel like structures, and increase the expression of angiogenesis-related genes [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 98%